2019
DOI: 10.22201/fesi.20072082.2019.12.72323
|View full text |Cite
|
Sign up to set email alerts
|

Historical Approach of the Fish Species Composition in Arroyo Moreno, Veracruz, Mexico

Abstract: <p>Arroyo Moreno (AM) is an estuarine water flow located between Boca del Río and Medellin municipalities from Veracruz State; although this estuarine habitat is situated in a state natural reserve, their environmental conditions had been altered in last decades by anthropogenic activities, which had caused changes on biotic communities including fishes. The aim of this contribution was to describe the temporal variation of fish species composition from Arroyo Moreno; an updated list of fish species was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…A study of eutrophication on the coast of the lower part of the Jamapa River, found in six sampling sites values of dissolved oxygen between the ranges of 3.41 to 6.19 mg L −1 , total nitrogen between ranges of 2.732 to 4.596 mg L −1 and temperatures of 27.67 to 30.30 °C, these values influence the water quality [37]. Local fishermen from the Jamapa river hydrological basin, in the Boca del Río municipality and field findings, indicate that species richness, abundance, fish sizes and their commercial use have decreased, as a result of the growth of the urban area, and the deterioration of the body of water and the negative effects on the fish population is also evident, in addition to that the characteristics of the water have been modified, mainly due to its poor quality [38].…”
Section: Impact On the Gulf Of Mexicomentioning
confidence: 99%
See 1 more Smart Citation
“…A study of eutrophication on the coast of the lower part of the Jamapa River, found in six sampling sites values of dissolved oxygen between the ranges of 3.41 to 6.19 mg L −1 , total nitrogen between ranges of 2.732 to 4.596 mg L −1 and temperatures of 27.67 to 30.30 °C, these values influence the water quality [37]. Local fishermen from the Jamapa river hydrological basin, in the Boca del Río municipality and field findings, indicate that species richness, abundance, fish sizes and their commercial use have decreased, as a result of the growth of the urban area, and the deterioration of the body of water and the negative effects on the fish population is also evident, in addition to that the characteristics of the water have been modified, mainly due to its poor quality [38].…”
Section: Impact On the Gulf Of Mexicomentioning
confidence: 99%
“…On the other hand, the impact that anthropic activities have on the aquatic environment of the Jamapa River basin is shown in the studies carried out in the Arroyo Moreno Protected Natural Area (ANPAM) by García-Villar et al, [6], where the temporal variation of the composition of fish species in the area, with the historical information collected with the fishermen and various statistical tools, they concluded that in the last two decades the richness, abundance and sizes of the fish species have decreased; particularly those used as a fishery resource, this effect is attributed to the use of this stream as a drainage of wastewater, which is a consequence of urban growth in the area and the lack of environmental management of this protected natural area.…”
Section: Introductionmentioning
confidence: 99%
“…The poeciliids are distributed throughout the entire national territory; however, the Usumacinta ichthyofaunistic region stands out for being one of the most studied, within this region there is many endemisms (Tobler et al, 2008;Miller et al, 2009). A relevant fact about this province is that large poecilid species live there, being the largest of them Belonesox belizanus family that can measure up to 20 cm in standard length (SL) while Poecilia catemaconis and Poeciliopsis catemaco occupy the second and fourth place respectively (Escalera, 2011;Pires et al, 2011;García-Villar et al, 2019).…”
Section: Distributionmentioning
confidence: 99%